EPISTEMOLOGI HUKUM ISLAM RASIONAL - EMPIRIK (AQLIYAH - TAJRIBIYYAH) - Somantri, Emma Dysmala (Sekolah Tinggi Hukum Bandung, 2012)
The rational and empirical study is not separated from some methods to produce legal source of aqliyyah, that is to say a rational reasoning which becomes a legal source based on ijtihad which has a relative accuracy level. It should be noted that legal sources of aqliyyah generally are referring to practical laws in the field of muamalah, and the knowledge obtained through al Tajribah is knowledge on phenomenon which is obtained through mind and sense collectively. This phenomenon occurs because of being created and reached by human ability to create it, and it occurs out of human ability to create it. When someone knows something based on experience, so the knowledge can be an argument (istidlal) to other people who do not experience.Keywords: rational, empirical, aqliyyah, tajribah.